Navigating Anti-Torture Measures: A Comparative Analysis of Georgian Legislation and International Law - Nano Vatcharadze (Theoretical Hypotheses and Empirical Results, 2023)
This article explores the multifaceted application of the prohibition against torture within the legal frameworks of both Georgian legislation and international law. Through an in-depth examination of the relevant legal provisions, definitions, and prevention mechanisms, this study aims to shed light on the intersection between domestic and international approaches to combatting torture. Real-world examples from court practices will be dissected to provide insights into the challenges and successes of implementing anti-torture measures.